(untitled) (International Journal of Natural Sciences, 2016)
Postpartum uterine infection is extremely important in dairy cattle. It is both common and detrimental to reproductive performance. The present study was conducted to investigate the factors responsible for postpartum uterine infection and its subsequent effect on fertility of crossbred dairy cows in Chatmohar Upazila, Pabna District. A total of 317 cows were selected and registered and then follow up them in postpartum period. Reproductive histories and data of the studied cows were assessed by direct interviewing and from record book of the owners and nearby government veterinary hospital. Totally 33 cows were found uterine infected (10.41%) in postpartum period. The case of pyometra was substantially higher in present study in contrast to others. The incidence of uterine infection puerperal metritis, pyometra and endometritis were 1.89%, 5.99% and 2.52% respectively. Dairy cattle calving season and parity reflected greatly on the incidence of uterine infection. Potentially significant (p<0.05) and higher incidence of uterine infection were associated with poor management system where minimum complications were found with good management practice (3.20%) compared to poor management farms. The dairy cows suffering from endometritis significantly showed prolonged days to first estrus interval, days open and number of services per conception and calving interval values (68.5±0.05 days; 115.4±0.4 days , 4.75±0.50, and 398±6 respectively) than normal healthy cows. Further researches in the near future must be directed for prevention of uterine infection, as most of effective treatments dont prevent the negative impacts of such disease upon dairy, reproduction and culling percentage within dairy herd. International Journal of Natural Sciences (2015), 5(2) 107-111